BiOBr/Bi2MoO6 composite in flower-like microspheres with enhanced photocatalytic activity under visible-light irradiation. Issue 16 (3rd February 2016) - Miao, Yingchun; Yin, Haibo; Peng, Lu; Huo, Yuning; Li, Hexing
Abstract : BiOBr/Bi2 MoO6 flower-like microspheres synthesized by a facile solvothermal method, exhibited high photocatalytic activity owing to the enhanced light harvesting via multiple-reflections and the reduced photoelectron–hole recombination. Abstract : BiOBr/Bi2 MoO6 composites in flower-like microspheres were synthesized by a facile solvothermal method. This photocatalyst could be activated by visible light owing to the narrow energy band gaps of both Bi2 MoO6 and BiOBr. The BiOBr/Bi2 MoO6 composites exhibited high activity in the photocatalytic degradation of rhodamine B and other organic pollutants under visible-light irradiation owing to enhanced light harvesting via multiple reflections inside the flower-like structure and due to the reduced photoelectron–hole recombination due to the formation of BiOBr–Bi2 MoO6 heterojunctions. The dominant active species during the photocatalytic oxidation of RhB were determined as photogenerated holes and ·O2 − was distinguished as the sub-main active site. The RhB mineralized into CO2 through the de-ethylation route via forming five intermediates.